Поиск новых митохондриальных и хлоропластных микросателлитных маркеров для генетических исследований популяций сосны сибирской кедровой в западной сибири - Орешкова, Н.В.; Седельникова, Т.С.; Пименов, А.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. Searching for informative markers of mtDNA and chlDNA in Pinus sibirica, which could become the basis for the identification of genetic differentiation of populations and determination of the relationship between the level of genetic variation and ecological and geographical conditions of their grouth. Methods. PCR analysis with 5 pairs of primers of mtDNA and 19 pairs of primers of chlDNA was conducted. Results. 24 pairs of PCR primers for amplification and genotyping of one mitochondrial and three chloroplast cytoplasmic loci of P. sibirica were tested. Conclusions. When analyzing mtDNA and chlDNA microsatellite loci, population of P. sibirica on eutrophic bog has appeared more polymorphic than population of P. sibirica from oligotrophic bog. Keywords: populations of Pinus sibirica, mtDNA, chlDNA, genetic polymorphism. Aims. Searching for informative markers of mtDNA and chlDNA in Pinus sibirica, which could become the basis for the identification of genetic differentiation of populations and determination of the relationship between the level of genetic variation and ecological and geographical conditions of their grouth. Methods. PCR analysis with 5 pairs of primers of mtDNA and 19 pairs of primers of chlDNA was conducted. Results. 24 pairs of PCR primers for amplification and genotyping of one mitochondrial and three chloroplast cytoplasmic loci of P. sibirica were tested. Conclusions. When analyzing mtDNA and chlDNA microsatellite loci, population of P. sibirica on eutrophic bog has appeared more polymorphic than population of P. sibirica from oligotrophic bog.